The Climate Challenge in Managing Water: Evidence Based on Projections in the Mahanadi River Basin, India - Kumar, M. Dinesh; Bassi, Nitin (Frontiers in Water, 2021)
This study analyzes the long-term changes in the rainfall and surface hydrology of the upper and middle sub-basins of Mahanadi, an inter-state river basin in eastern India that experiences climate-induced hydrological extremes, and draws implications for the sustainability of irrigation and drinking water supplies. The likely impacts of rainfall changes on surface flow were also modeled. A Water Evaluation and Planning (WEAP) model was set up (beginning June 2009 and ending May 2050) to analyze the future water balance of the basin for the expected changes in socio-economic conditions. The model was also run for future scenarios that considered different water management interventions, and hydrological consequences of climate variability and change. The model results showed that there would be a water deficit, about 2,182 million cubic meters (MCM) by 2050 (20% of the demand) even under the business-as-usual scenario. The gap is expected to widen to 5,005 MCM (25% of the demand) under a high growth scenario. Further, the water demand management interventions in agriculture would be able to reduce the overall demand for water in the basin to some extent, while it would also reduce the supplies slightly due to a reduction in return flows occurring as a result of irrigation efficiency improvement. The water deficit under this scenario will reduce to about 2,773 MCM in 2050. Under the predicted changes in climate, the water deficit is expected to reduce further (will be 1,684–2,373 MCM in 2050) due to an increase in supplies owing to an increase in the catchment yields resulting from higher rainfall. While there will be a significant amount of outflow from the two sub-basins in all the scenarios in most future years (ranging from 25,286 MCM to 28,697 MCM in 2050), during drought years, the water deficit in the upper basin areas will increase slightly, but with a significant reduction in the outflows to the lower sub-basin areas by 2046–47 (will be about 11,311 MCM). These results indicate that there is a need for building more water storage/diversion infrastructure to detain floodwaters during wet years that can provide buffer storage for the dry years.